Dossier Presentation: Power in Latina America: a tribute to profesor Glaucio Soares - Telles, Helcimara; Silva, Joscimar Souza; Ruiz, Letícia (Revista Debates, 2022)
This dossier, organized by LATICOM/ALACIP (Grupo de Investigación en Comunicación Politica y Comportamiento Electoral en América Latina, da Asociación Latinoamericana de Ciencia Politica) is a tribute to keeping alive the memory of Gláucio Ary Dillon Soares, one of the most important researchers in Science Brazilian and Latin American Politics and Sociology.